Fear Of Missing Out Dan Repurchase Decisions Dalam Gacha Games: Perspektif Indonesia - Dharma, Rio Adi (Syntax Corporation, 2025)
The phenomenon of Fear of Missing Out (FoMO) has become a significant psychological force in driving repurchase decisions in gacha games. The study reviewed the literature over the past five years that discussed how FoMO works through the creation of a sense of urgency and a concern of detachment, which ultimately influences repetitive consumption behaviors. Focusing on the context of Indonesia—one of the fastest-growing mobile game markets in the world—this study explores the demographics of local players, shopping habits, and the influence of collectivist culture on the strengthening of FoMO. This analysis includes the integration of theoretical frameworks such as self-determination theory, social comparison theory, and loss aversion, as well as new models such as the FoMO-driven spiral and the FoMO marketing appeal model. The findings show that gacha game design strategically leverages FoMO through time-limited events, exclusive items, and social influence within the player community. The study also highlights the potential negative impact of FoMO on consumer well-being as well as the need for an ethical approach in monetization strategies. Practical and theoretical implications are put forward to encourage more contextual and multidisciplinary follow-up research, especially in emerging markets such as Indonesia.